Petrogenesis and tectonic significance of Neoproterozoic basaltic rocks in South China: From orogenesis to intracontinental rifting - Li, X.; Wang, Xuan-ce; Li, W.; Li, Zheng-xiang (Pergamon-Elsevier Science Ltd, 2008)
Neoproterozoic igneous rocks are widespread in South China. Understanding the nature and petrogenesis of these rocks has significant implications for the regional tectonic evolution and the assembly and break-up of the supercontinent Rodinia. However, there is still a hot debate on the petrogenesis and tectonic affiliations of these rocks. We carried out in this study a systematic compilation of geochemical data for the Neoproterozoic basaltic rocks in South China, and used these data to investigate their primary melt compositions, melting conditions and their mantle potential temperatures and compositions, with the aim of providing new constraints on their origin and petrotectonic associations. In combination with other aspects of geological observations, we proposed a geodynamic evolution model for the lithosphere of the South China Block involving late Mesoproterozoic-early Neoproterozoic orogenesis and middle Neoproterozoic intracontinental rifting.